ANALISIS NILAI INDEKS DMF-T SISWA YANG MENGGOSOK GIGI MENGGUNAKAN AIR SUMUR DI WILAYAH PANTAI SWARANGAN - Aida Yanti; Widodo Widodo; Ika Kusuma Wardani; Riky Hamdani; Muhammad Yanuar Ichrom Nahzi (Universitas Lambung Mangkurat, 2024)
Background: Tooth decay, especially caries, is the most common disease and disrupts oral health in the community. The prevalence of people who have oral health problems in Indonesia is 45,3% with a percentage in South Kalimantan Province of around 46,9% in 2018 with a DMF-T index value of 7,2. Oral health problems in South Kalimantan Province with a high prevalence, one of which is in Tanah Laut District, most of the people in Swarangan Village, Tanah Laut District live on the coast and use dug well water to brush their teeth so that they have oral health problems with a high prevalence of 44,73%, the well water used by the community gets supply from the sea, so that it can interfere with the concentration of minerals in the water used. Objective: Analyze the DMF-T index value of SMPN 6 Jorong students who brush their teeth using dug well water based on a distance of 140-712 meters and a distance of 713-1.300 meters from the beach. Methods: This study used an analytic observational method with a cross sectional approach. Respondents and samples were taken with simple random sampling technique, the number of respondents in this study was 50 people. Results: The study shows the DMF-T index in students who brush their teeth using dug well water based on a distance of 140-712 meters is 6.0, while the DMF-T index in students who brush their teeth using dug well water based on a distance of 713-1.300 meters is 4,28 with the p value obtained is 0,182>0,05. Conclusion: There is no significant difference in DMF-T index values between students who use dug well water at a distance of 140-712 meters and a distance of 713-1.300 meters from the beach.Keywords: DMF-T, Distance of well from shore. ABSTRAK Latar belakang: Kerusakan gigi terutama karies adalah kondisi yang paling umum ditemui dan berpotensi mengganggu kesehatan gigi dan mulut masyarakat. Pada tahun 2018, prevalensi masalah kesehatan gigi dan mulut di Indonesia mencapai 45,3%. Di Provinsi Kalimantan Selatan, angka ini mencapai 46,9%, dengan indeks DMF-T 7,2. Salah satu daerah dengan prevalensi tinggi adalah Kabupaten Tanah Laut, terutama di Desa Swarangan, dimana sebagian besar penduduknya tinggal di pesisir pantai dan menggunakan air sumur gali yang suplai airnya berasal dari laut. Kondisi ini dapat memengaruhi konsentrasi mineral dalam air yang digunakan untuk menggosok gigi, yang kemudian berkontribusi pada tingginya prevalensi masalah kesehatan gigi dan mulut mencapai 44,73%. Metode: Penelitian ini menggunakan metode observasional analitik dengan pendekatan cross sectional. Sampel diambil dengan teknik simple random sampling, besar responden pada penelitian ini sebanyak 50 siswa. Hasil: Penelitian menunjukkan bahwa rata-rata nilai indeks DMF-T pada siswa yang menggunakan air sumur gali dalam rentang jarak 140–712 meter adalah 6,0. Sementara itu, pada siswa yang menggunakan air sumur gali dalam rentang jarak 713–1.300 meter memiliki rata-rata indeks DMF-T 4,28. Analisis statistik menunjukkan nilai p sebesar 0,182, > 0,05. Kesimpulan: Tidak terdapat perbedaan nilai indeks DMF-T antara siswa yang menggunakan air sumur gali jarak 140–712 meter dengan jarak 713-1.300 meter dari pinggir pantai.